2017
DOI: 10.1080/0142159x.2017.1340636
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review of the published literature on team-based learning in health professions education

Abstract: A substantial body of literature examines the effect that TBL has on traditional measures of achievement. However, many dimensions of TBL have not been well studied, including Teacher Decisions about TBL, Contextual Factors that affect TBL, Learners' Engagement, and Pattern of Engagement within Teams. Future research in these areas could determine the best use of TBL in HPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
245
0
27

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(286 citation statements)
references
References 63 publications
7
245
0
27
Order By: Relevance
“…Previous studies have shown that the active methodology has been well accepted in Physical therapy courses, when approaching contents related to the understanding of the health-illness process [6,15] and the results suggest teaching practices that favor a dialogued and critical education [2,3,22]. However, little evidence shows the TBL method more specifically for this undergraduate course.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Previous studies have shown that the active methodology has been well accepted in Physical therapy courses, when approaching contents related to the understanding of the health-illness process [6,15] and the results suggest teaching practices that favor a dialogued and critical education [2,3,22]. However, little evidence shows the TBL method more specifically for this undergraduate course.…”
Section: Discussionmentioning
confidence: 81%
“…In the first group, it was not possible to adopt the method due to the students' own preferences, who questioned the fact that the evaluation preceded the professor's teaching. Such strangeness results from the hegemonic model of health education founded on the hierarchy between professor and student, the dichotomy between practice and theory and the struggle to construct different knowledges collectively [17,22]. In a pharmacy undergraduate course [21], when the students were first taught through the TBL method and then the traditional method was adopted, they refused expository lessons and showed interest to continue the active method of learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many interventions have been tested to investigate the effectiveness of different teaching methods, and comprehensive pragmatic and systematic reviews of evidence-based strategies for the teaching of undergraduate RMDs have been published [74,104]. Examples of successful teaching strategies include the following: small interactive group sessions [81,108,109], flipped classroom learning [110], the use of patient educators/partners [109,[111][112][113], team-based learning [114,115], peer-assisted learning [116,117], e-learning or computer-assisted learning as a useful adjunct [118][119][120][121] and the use of MSK ultrasound to facilitate the learning of anatomy [122][123][124]. Educators in the field of RMDs have been encouraged to embrace new teaching strategies and learning styles [40,82,93].…”
Section: Learning Methods and Interventionsmentioning
confidence: 99%
“…(1) students' preparation of an assigned topic with guided focused pre-reading resources, (2) demonstration of their knowledge through individual (IRAT) and group readiness assurance tests and finally, (3) group problem-solving exercises of real-world scenarios through the application of their learned concepts. 11,12 At the University of Notre Dame Australia School of Medicine Sydney, we designed and implemented a modified format of the classical TBL model with positive outcomes. The medical course in the University of Notre Dame Australia School of Medicine Sydney is a graduate entry, 4-year medical programme, and anatomy is taught mainly during the first 2 years.…”
mentioning
confidence: 99%